Haemodynamic Changes & Complications between Unilateral and Bilateral Spinal Anesthesia in Elderly Type-2 Diabetic Patient Undergoing Hemiarthoplasty – A Comparative Study (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: During spinal anesthesia, extend of sympathetic blockade causes hemodynamic instability,such as hypotension and bradycardia.It can lead to develop cardiac arrest in some cases. Elderly patientdo not compensate these haemodynamic change easily because of aging process leads some physiologicalchanges in all system especially on cardio vascular system e.g; decreased elasticity of vessels, decreasedvascular and myocardial compliance and also decreased autonomic responsiveness. It is hypothesizedthat unilateral spinal anesthesia restrict the spread of hyperbaric bupivacaine to one side only (dependentside) thus sparing the opposite sympathetic chain and hence would cause less haemodynamic changes.Materials & Methods: This cross sectional study, took place in the department of Anaesthesiology andSICU, BIRDEM General Hospital, Shahbag, Dhaka. A total 60 elderly (age-60 to 80 years), ASA grade IIand III, type-2 Diabetic patients scheduled for hemiarthoplasty were enrolled in this study. Patients weredivided into two groups U & A, 30 patients in each. Subarachnoid (spinal) anaesthesia was performed inall patients with 0.5% hyperbaric bupivacaine intrathecally, at L3 - L4 interspinous spaces, with 25GQuinke’s spinal needle. Patients of group U were kept in lateral decubitus position which was maintainedfor 15 minutes after injecting bupivacaine and patients of group B were kept in supine position. Changesof BP, pulse and development of any complication was recorded in 5 minute interval after spinal anesthesia.All the informations were recorded in preformed data collection sheet.Result: Compared with group U, group B showed statistically significant increase inheart rate at 10 minafter spinal anesthesia (p